2023
DOI: 10.1071/cp22105
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis and identification of QTLs associated with yield-enhancing traits in Oryza sativa IR64 × Oryza glaberrima interspecific backcross populations

Abstract: Context Broadening the gene pool of staple food crops by incorporating desirable genes from wild/relative species is way to achieve higher genetic gains. The African rice species Oryza glaberrima Steud. is a source of genes for genetic improvement of Oryza sativa L. to various biotic and abiotic stresses. Aim The study was undertaken to identify genomic regions associated with yield and yield-related traits in interspecific backcross mapping populations derived from variety IR64 (O. sativa indica) × O.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…with heat stress tolerance. Bharamappanavara et al (2023) determined genomic regions related to yield traits in mapping populations obtained from backcrossing of Oryza sativa indica and O. glaberrima. The authors reported a QTL hotspot near marker RM510, and a QTL qGY-4.1 that is associated with grain yield and can be used for increasing yield in O. sativa cultivars via molecular breeding.…”
mentioning
confidence: 99%
“…with heat stress tolerance. Bharamappanavara et al (2023) determined genomic regions related to yield traits in mapping populations obtained from backcrossing of Oryza sativa indica and O. glaberrima. The authors reported a QTL hotspot near marker RM510, and a QTL qGY-4.1 that is associated with grain yield and can be used for increasing yield in O. sativa cultivars via molecular breeding.…”
mentioning
confidence: 99%